Peningkatan Kemampuan Kolaborasi dalam Pembelajaran IPA pada Siswa Kelas II MIS Amir Al-Jannah Tippulue dengan Media Couple Cards - Adliana, Andi Dilla (Madrasah Ibtidaiyah Research Journal, 2023)
This study aims to determine the effectiveness of using Couple Cards media to improve collaboration skills in learning science in class II students of MIS Amir Al-Jannah Tippulue. The type of research used is quantitative research using the Pre-Experimental approach using the One-Group Pretest-Posttest Design conducted at MIS Amir Al-Jannah Tippulue in class II with a total sample of 21 students. Data collection techniques used observation sheets and questionnaires on student collaboration skills. Data were analyzed using descriptive statistical analysis. Then do an analysis to test the hypothesis using the SPSS version 22 application. The results of this study indicate that based on the Paired Sample T-Test it shows a t-count of 12,997 with a significance value of 0,000. Then the tcount value is compared with the ttable value at a significance level of 5%, the ttable is obtained from the t distribution list with probability (1-Î±) to obtain a ttable of 2,08596. This shows that the value of tcount is greater than ttable (12,997>2,08596). When compared with a significance value of 0,000 which is less than a significance of 0,05 (0,000<0,05), the hypothesis in this study is stated that H0 = rejected and H1 = accepted. Based on the results of the calculation of the N-Gain Score which shows the average value of students is 61,54%, it is included in the quite effective category. With a minimum N-Gain Score of 25,49% and a maximum of 100%. Thus the researcher stated that the Couple Cards media was effective enough to improve the collaboration skills of class II students of MIS Amir Al-Jannah Tippulue.